Experimental prototype for learning wave phenomena - Vázquez Méndez, Wilfredo (2024)
Physics is one of the sciences in which few students feel intrinsically attracted and motivated. The reasons are diverse, one of them being the lack of extrinsic motivation. As a result, it is observed that they have more difficulties in learning this area. For this reason, the present research was developed with the objective of designing and evaluating the effectiveness of a practical experimental prototype that facilitates learning in the content of mechanical waves, refraction and reflection, through a quantitative approach study, experimental type, on a sample of 8 eleventh grade students and the area teacher of the Ramón Alejandro Roque Ruiz school, from the community of Santa Isabel in the municipality of Somoto, selected with simple random probabilistic sampling. Three instruments were used to collect data that were applied to students and the teacher, which are: the questionnaire, the standardized test and the observation guide. The results show that the students improved their level of learning about wave phenomena, especially in the thematic field of refraction and reflection of mechanical waves.